Sosialisasi Mengenai Gizi Seimbang Dan PHBS (Pola Hidup Bersih Dan Sehat) Guna Mengurangi Angka Stunting Di Desa Sumbersalak Kecamatan Ledokombo Kabupaten Jember - Faishal Muqtadir Tamim; Agung Ghani Putra; Riziqi Abista Bagaskara; Kartika Zenithia Liveranny; Lu’luul Izzatul Fitriyah; Kholifatul Sa’diyah; Zeynab Varadita; Zulva Oktovia (CV. ITTC INDONESIA, 2023)
Stunting is a chronic nutritional problem due to lack of nutrition in the long term resulting in growth disturbance in children or what is called a condition of failure to thrive in the womb until the baby is 2 years old. Clean and healthy living behavior is one of the indirect factors that causes a person's nutritional and health status, especially in toddlers. Efforts to prevent and reduce stunting rates can be done by adopting a healthy and clean lifestyle and also getting used to eating a balanced diet. The purpose of holding community service with a focus on the Real Work Lecture work program with the theme of Stunting Free Village is so that people are more aware of the dangers of stunting and can help reduce stunting rates in the future. The method used was to hold socialization with the theme of balanced nutritional food and a clean and healthy lifestyle with the target of children through RA Nuruzzaman's guardians in Sumbersalak Village, Paluombo hamlet who attended the activity around 30 parents of students whose children attended RA Nuruzzaman's foundation. From the results of observations in Sumbersalak Village, there are still many people who still do not know how to process waste properly and lack self-awareness about the environment and lack of mother's knowledge about food management and balanced nutrition, especially in the first 1000 days of life.